A dynamic model of bank behaviour under multiple regulatory constraints - Markus Behn; Claudio Daminato; Carmelo Salleo (European Central Bank (ECB), 2019)
We develop a dynamic structural model of bank behaviour that provides a microeconomic foundation for bank capital and liquidity structures and analyses the effects of changes in regulatory capital and liquidity requirements as well as their interaction. Our findings suggest that adjustments in both types of requirements can have an impact on loan supply, with considerable heterogeneity across banks and over time. The model illustrates that banks' reactions depend on initial balance sheet conditions and reconciles evidence on short-term reductions in loan supply with findings suggesting that better capitalized banks are better able to lend in the medium- to long-term.
Keywords: G21; G28; G32; 330; bank regulation; capital structure; liquidity structure; structural model